DRUG SCREENING FOR ERO1α INHIBITORS - Khojayeva, Kamilla (Nazarbayev University School of Medicine, 2025)
ERO1α (Endoplasmic Reticulum Oxidoreductin 1 Alpha) is an ER-resident oxidase involved in oxidative protein folding and redox homeostasis. Its overexpression has been linked to poor prognosis in various cancers, including triple-negative breast cancer (TNBC). This study aimed to investigate the effects of selected repurposed drugs - resveratrol, indomethacin, ribavirin, and acyclovir - on ERO1α expression, oxidative stress, and cell proliferation in breast cancer cells. MDA-MB-231 cells, a TNBC model, was selected based on significantly higher ERO1α expression compared to other cell lines. MTT assays revealed that resveratrol and indomethacin reduced cell viability in a dose-dependent manner, with resveratrol demonstrating greater cytotoxicity. Western blot analysis showed that both compounds reduced ERO1α protein levels, with statistically significant decreases observed at 500 and 250 µM of resveratrol and 2.4 and 1.2 mM of indomethacin. In addition, ROS levels measured by the d-ROMs test were significantly reduced by both resveratrol and indomethacin. These findings suggest that resveratrol and indomethacin may have anticancer effects through modulation of oxidative stress and ERO1α expression in TNBC cells.
Keywords: ERO1α; breast cancer; resveratrol; indomethacin; oxidative stress; Type of access: Embargo